Throught the eye of a needle : the Africa debt report : a country by country analysis - Owusu, Kwesi; Clarke, Sarah; Croft, Stuart; Garrett, John (London: Jubilee 2000 Coalition, 2000)
"Written by Kwesi Owusu, Sarah Clarke, Stuart Croft, John Garrett"